2023
DOI: 10.3390/healthcare11152192
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physical Activity on Health-Related Quality of Life of Older Adults Using Newly Developed Health-Related Quality of Life Tool for the Korean Population

Abstract: This study aimed to investigate the effect of physical activity on health-related quality of life. Data from the 2019 Korean National Health and Nutrition Examination Survey were used. The participants were 1495 (56.7% women) older individuals older than 65 years of age. A one-way analysis of variance (ANOVA) and multiple regression analysis were performed to determine the effect of walking and strength exercise on the health-related quality of life using the Korean version of the health-related quality of lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Moreover, it has a lower ceiling effect as compared with the EQ-5D [53]. For these reasons, the HINT-8 has been used as an HR QOL assessment tool for the KNHNES studies since 2019 [18,52,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has a lower ceiling effect as compared with the EQ-5D [53]. For these reasons, the HINT-8 has been used as an HR QOL assessment tool for the KNHNES studies since 2019 [18,52,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported that smokers are underweight {lower body mass index (BMI)} when compared to non-smokers [10,19,30]. However, evidence suggests that smokers suffer from developing central fat accumulation, mostly seen among female smokers [30].…”
Section: Smoking and Body Compositionmentioning
confidence: 99%
“…Various studies have reported that smokers are underweight {lower body mass index (BMI)} when compared to non-smokers [10,19,30]. However, evidence suggests that smokers suffer from developing central fat accumulation, mostly seen among female smokers [30]. Since nicotine has a significant suppressing component, research has identified it as the reason smokers have a lower BMI than non-smokers [28][29][30].…”
Section: Smoking and Body Compositionmentioning
confidence: 99%
See 2 more Smart Citations